Tent screws: Predictable guided bone regeneration - Farhan Durrani; Preeti Singh; Aishwarya Pandey; Kaushal Pati Tripathi; J P Vishnu; Fouzia Imran; Aabida Taslim (Wolters Kluwer Medknow Publications, 2023)
Bone regeneration of large maxillary and mandibular alveolar ridge defects is clinically challenging. Various techniques have been described for the reconstruction of these deficiencies before implant placement. The tent screw-pole technique is one of the effective methods available for clinicians to perform the predictable functional and esthetic reconstruction. The aim of this prospective report was to evaluate clinical and three-dimensional radiographic analyses of two patients treated with xenograft and particulate autogenous bone using tenting screws for regeneration of compromised partial edentulous ridges.